Modulation of Gut Microbiota, Nutrient Transport Gene Expression, and Growth of Red Hybrid Tilapia (Oreochromis sp.) Fed with Black Soldier Fly (Hermetia illucens) by Oral Probiotics - Latifah, Ma'rufa Nurul; Murti, Fauziah Arelia Usmiara; Helmiati, Senny; Ismail, Norshida; Syakuri, Hamdan; Istiqomah, Indah; Murwantoko, Murwantoko; Isnansetyo, Alim (Jurnal Perikanan Universitas Gadjah Mada, 2024)
Maggot Black Soldier Fly (BSF) is a nutritionally rich alternative food for fish. The slow digestibility requires the combination with other technologies to produce fish with excellent growth. This study aims to investigate the impact of probiotic application on the growth, microbiome, and gene expression in the intestines of tilapia-fed black soldier fly (BSF) larvae. Tilapia intestines were examined after two months of rearing with three replications and two treatments: A) 30% maggots and 70% commercial pellets with probiotics, and B) 30% maggots and 70% commercial pellets without probiotics. We discovered that probiotics have a significant impact on the gut microbiomes of fish and their absolute growth. The amplicon sequence variant in the probiotic treatment (A) was 25, with dominance by Cetobacterium, Acinetobacter, Enhydrobacter, and Gemmobacter, while the non-probiotic treatment (B) was 8, with dominance by Cetobacterium and Turicibacter. The probiotic treatment increased the expression of Ghrelin, Muc-2, IL-1β, and I-FABP genes, but not the CD36 gene. These findings suggest oral probiotics can help boost tilapia production when fed maggot black soldier fly (Hermetia illucens).